Immunomodulatory role of metalloproteinase ADAM17 in tumor development - Wang, Kai; Xuan, Zixue; Liu, Xiaoyan; Zheng, Meiling; Yang, Chao; Wang, Haiyong (Frontiers in Immunology, 2022)
ADAM17 is a member of the a disintegrin and metalloproteinase (ADAM) family of transmembrane proteases involved in the shedding of some cell membrane proteins and regulating various signaling pathways. More than 90 substrates are regulated by ADAM17, some of which are closely relevant to tumor formation and development. Besides, ADAM17 is also responsible for immune regulation and its substrate-mediated signal transduction. Recently, ADAM17 has been considered as a major target for the treatment of tumors and yet its immunomodulatory roles and mechanisms remain unclear. In this paper, we summarized the recent understanding of structure and several regulatory roles of ADAM17. Importantly, we highlighted the immunomodulatory roles of ADAM17 in tumor development, as well as small molecule inhibitors and monoclonal antibodies targeting ADAM17.